DESIGNING ENGLISH MATERIALS BY USING TAPAK TUAN FOLKLORE - Ichsan Darmawan; Saut Gultom; Maranata Lumban Batu; Yenita Sembiring (English Language Teaching Prima Journal (ELT), 2022)
Tapaktuan is not only famous for its natural beauty but also because of many folklores that grew from this city, like a disobedient child who is said to be almost similar to Malin Kundang's story, but this story has a version from Tapaktuan City, and the most famous is the story of a dragon and a very powerful master. The majority of livelihoods in Tapaktuan are nutmeg farmers, rice fields and fishermen. The unique thing is that the economy is very rich in natural resources but the people there are not rich. Because it is said that their ancestors once said "this city will not be rich, but if it is for food, it must be enough". The first people who live in Tapaktuan are the Minang tribe, therefore the Tapaktuan community is mostly inhabited by the Minang tribe, Acehnese tribe, Kluet tribe and Pak Pak tribe. According to the results of research that has been conducted, the Minang tribe has its own uniqueness where the tribe must marry their fellow tribesmen. Through the results of research and discussion that has been conducted out in chapter III, then conclusions can be formulated regarding the reading materials that found in the folklore of Tapak Tuan. Here, through the reading materials that has been provided for readers may explore the true story legend of Tapak Tuan to give them insight. The information of Tapak Tuan folklore that has been gathered through the right informant is to design reading materials that give readers a clear information and in this reading materials, all the details are explained that readers need in the whole story to give readers a chance a deeper understanding. Researchers also provide a clear explanation and easy to understand the chronology of Tapak Tuan folklore. This shows that folklore is very useful to be used as reading material that has cultural values and good moral that can be meditated and applied by the readers in their daily life.